1987
DOI: 10.1007/bf01784306
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of determination of right ventricular ejection fraction by radionuclide imaging: Assessment by the statistical method of variance components

Abstract: Confidence limits for single and repeat measurements of right ventricular ejection fraction (RVEF) were established by means of a model based on the statistical method of variance components. A total of 80 subjects (age 23 to 74 years) were examined by two radionuclide methods 1) gated first-pass (fp) technique performed in a standard 30 degrees right anterior oblique projection, and 2) multigated equilibrium imaging (muga) in an individual left anterior oblique view, applying with both methods separate end-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Accordingly, it is difficult to evaluate changes in RVEF over time if measured by different methods at different time points. We and others (Hoilund-Carlsen et al, 1987;Pattynama et al, 1995) found that the LoA between repeated RVEF measurements with the same technique were lower both for FP and MRI. When measured by GBPS technique, the lower normal value of RVEF was even lower namely 0AE40.…”
Section: Rvef Mri Fp Gbpsmentioning
confidence: 64%
See 1 more Smart Citation
“…Accordingly, it is difficult to evaluate changes in RVEF over time if measured by different methods at different time points. We and others (Hoilund-Carlsen et al, 1987;Pattynama et al, 1995) found that the LoA between repeated RVEF measurements with the same technique were lower both for FP and MRI. When measured by GBPS technique, the lower normal value of RVEF was even lower namely 0AE40.…”
Section: Rvef Mri Fp Gbpsmentioning
confidence: 64%
“…Accordingly, it is difficult to evaluate changes in RVEF over time if measured by different methods at different time points. We and others (Hoilund‐Carlsen et al. , 1987; Pattynama et al.…”
Section: Discussionmentioning
confidence: 75%
“…A RAO projection offers the best separation of right atrium and ventricle as the tricuspid valve plane can be identiffed in both right ventricular end-diastole and endsystole. ECG-gating improves reliability of the method [2,3,14] and it has been shown that a double ROI firstpass technique (separate right ventricular ED and ES ROIs) has higher accuracy [3] and precision [4,15] in determining RVEF than a single ED ROI technique or an equilibrium ECG-gated method. Rezai et al [3] showed that the tricuspid valve moves from 9 to 33% of the right ventricular long axis from ED to ES which explains the necessity of the double ROI method.…”
Section: Discussionmentioning
confidence: 99%
“…H¢ilund-Carlsen et al [15] have performed an interobserver, intraobserver, and interrecording variability study of first-pass measurement of RVEF with a method comparable to our method I (with no background subtraction). Their results were comparable to the present ones regarding inter-and intraobserver variability, but in their interrecording analysis, the second recording was separated from the first one by 1-4 weeks [15]. Our method for determining mPTT had a high precision in the inter-and intraobserver context but there was a systematic difference in the interrecording study as mPTT of R2 was higher than during R1.…”
Section: Discussionmentioning
confidence: 99%
“…Right-ventricular ejection fraction was determined by a first-pass technique in a standard 30° right anterior oblique projection applying separate end-diastolic and end-systolic regions of interest [8]. The 95% confidence limits of left ventricular ejection fraction (LVEF) based on a single measurement equalled the measured value B 0.06 [9]. Leftventricular variables were determined by multigated equilibrium imaging using an individually adjusted left anterior oblique view for optimal septal separation.…”
Section: Methodsmentioning
confidence: 99%